Beginners : the joy and transformative power of lifelong learning - Vanderbilt, Tom (Alfred A. Knopf, 2021)
"Why do so many of us stop learning new skills as adults? Are we afraid to fail? Have we forgotten the sheer pleasure of being a beginner? Or is it simply a fact that you can't teach an old dog new tricks? Inspired by his young daughter's insatiable need to know how to do almost everything, and stymied by his own rut of mid-career competence, Tom Vanderbilt begins a year of learning purely for the sake of learning. He tackles five main skills (and picks up a few more along the way), choosing them for their difficulty to master and their distinct lack of career marketability--chess, singing, surfing, drawing, and juggling." -- Amazon.com.